Praktický význam spirituality v procese zvládania neobvyklých mentálnych symptómov - Paulík, Matej (Religio, 2020)
This article is primarily theoretical. The main purpose is to outline a research approach that would contribute to a social-scientific view of alternative spirituality in the context of everyday life. I will explore the possible meanings and functions that alternative spirituality can have as one of the cultural resources that is used to cope with unusual physical and mental symptoms. Typical examples of such symptoms are hearing voices, communication with non-human beings, strange feelings in the body, uncontrollable body movement, and changes in sensory perception. These symptoms can result in a variety of personal and professional crises. I try to illustrate the proposed theoretical approach to the study of spirituality using empirical data from my dissertation research, which were obtained through biographical interviews. The basic criterion for the selection of communication partners and their inclusion in the research was their experience with unusual mental and physical symptoms and their effort to manage this experience through the concept of psychospiritual crisis. I try to show how alternative spirituality in the context of the concept of psychospiritual crisis helped my communication partners to cope with their symptoms through a new understanding of this experience. To do this, I employ methodological and theoretical tools from various scientific fields, such as the anthropology of health and illness, transcultural psychiatry, and science and technology studies.